Biological Effects of Low-Dose Radiation Therapy: From Mechanistic Aspects to Translational Approaches and Challenges - Donaubauer, Anna-Jasmina; Mogge, Lia; Schubert, Philipp; Fietkau, Rainer; Ott, Oliver; Frey, Benjamin; Gaipl, Udo (Seminars in Radiation Oncology, 2025)
Low dose radiation therapy (LDRT) is commonly applied for its pain and symptom-relieving effects in the treatment of different benign diseases, such as chronic degenerative and inflammatory, or hyperproliferative disorders. Most clinical trials report a beneficial therapeutic effect of LDRT and further, robust preclinical evidence on the biological modes of action of LDRT is existent. In chronic degenerative and inflammatory diseases such as osteoarthritis, LDRT can ameliorate inflammatory processes and impacts positively on the bone metabolism. A key mechanism is the modulation of the endothelium and the phenotype of macrophages. In the bone, the deposition of new bone matrix is supported, while bone degradation is diminished. In hyperproliferative disorders, the main mode of action is the inhibition of the differentiation and proliferation of fibroblasts and myofibroblasts, along with a modulation of inflammatory mediators, such as cytokines. Even though comprehensive preclinical evidence supports the use of LDRT, biological mechanistic insights from randomized clinical trials is mostly missing for LDRT and indicates a significant translational gap. Apart from preclinical data, the evidence for LDRT is based largely on observational clinical trials, with only limited randomized and placebo-controlled trials available. In the future, rigorously designed randomized disease-specific studies with standardized protocols, translational research programs and objectifiable clinical and biological endpoints are needed to establish LDRT as precise and evidence-based therapy.
CRIS-Team Scopus Importer:2025-12-12